2009
DOI: 10.4028/www.scientific.net/kem.417-418.725
|View full text |Cite
|
Sign up to set email alerts
|

Durability Studies for Complete Dentures

Abstract: The complete dentures are realized by different acrylic resins and different technologies. These materials are fragile and frequently appear crack and fractures of these dentures. Also, theses materials as well as the technologies of performing these dentures are expensive. In order to avoid the ultimate failure of the complete dentures, for each case there is necessary a numerical simulation as a preliminary stage before the effective performance of the denture. In order to realize the numerical simulation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 7 publications
0
7
0
Order By: Relevance
“…But, despite the efforts made to continuously improve their physical, mechanical and aesthetic properties thereby cause side effects regarding their biocompatibility. These situations may lead to local lesions which can prove extremely unpleasant for the patient [16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…But, despite the efforts made to continuously improve their physical, mechanical and aesthetic properties thereby cause side effects regarding their biocompatibility. These situations may lead to local lesions which can prove extremely unpleasant for the patient [16].…”
Section: Discussionmentioning
confidence: 99%
“…The results obtained with TNF-alpha test are eloquent for cytotoxic detection of early signs of allergy and inflammation by measuring the endotoxins from the patient serum. It is always recommended to associate multiple types of clinical tests and these should always be histologically confirmed [16].…”
Section: Tnf Alpha Testmentioning
confidence: 99%
“…In [ 50 ], the fatigue behavior of the complete denture, which is fabricated from the ‘SUPERACRYL PLUS’ material (Spofadental a.s., Jicin, Czech Republic), was assessed with the ‘ANSYS’ FEM-based commercial software package. In this case, Weller’s curves were drawn for the flat samples.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results were presented in terms of the safety factor variation. The authors of [ 50 ] suggested implementing a FEM-based procedure for eliminating the total damage (accidents), which is a characteristic of complete dentures.…”
Section: Introductionmentioning
confidence: 99%
“…Continuous development and progress of polymer's industry with applications in general and dental medicine was of great importance for the health domain. Using various types of resins for restorations in the oral cavity is beneficial from childhood till geriatric period [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%